Social development: traditions and contemporary approaches to study - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes traditional approaches to social development research: evolutionary and civilizational (idea of history circles). The main features of evolutionary tradition are explicated. Special attention is given to formational approach. Essence of antipodes (K. Popper, R. Budon) is presented. Peculiarities of history circles are analyzed. It is shown that the beginning of the 21st century is the period of active search for new paradigms. The main conclusion is that the main tendencies are the following: attention to special role of individuals, social groups and movements in social changes; principal plurality of ways of communities’ development.